Perspektif Al-Qur’an terhadap Pembagian Harta Waris di Desa Pedamaran Kecamatan Pedamaran Kabupaten Ogan Komering Ilir (Studi Living Qur’an) - Nova Anggraini; Apriyanti Apriyanti; Kamaruddin Kamaruddin (Jurnal Semiotika Quran, 2022)
This article is intended to examine the distribution of inheritance in Pedamaran 1 Village which seems to be more inclined to favor girls, so that it seems contrary to Islamic inheritance law. Whereas according to the majority of scholars, QS. al-Nisa' verse 11 states that the share of inheritance for girls is half of the inheritance for boys. This research is a field research using the living qur'an method. The research location is Pedamaran 1 Village, Pedamaran District, Ogan Komering Ilir Regency. The results of this study indicate that the distribution of inheritance in Pedamaran 1 Village, Pedamaran District, Ogan Komering Ilir Regency (OKI) still adheres to customs. The factor that makes only the eldest daughter inherit is because she has the responsibility to take care of her parents, especially when they are old or sick. Girls usually understand their parents better than boys. Even so, in reality this division of inheritance does not cause disputes among family members.